The relationship between life satisfaction and alienation level of disabled athletes (Kayseri Case) - E. Özkatar Kaya; A. Pekel (H.S. Skovoroda Kharkov National Pedagogical University, 2019)
Background and Study Aim: The aim of this study is to investigate the relationship between life satisfaction and alienation level of disabled athletes living in Kayseri. Material and Methods: The population of the study consists of 421 disabled athletes engaged in sports. The sample consisted of 109 disabled athletes identified by simple random sampling method. The study was performed by scanning method and the data was collected by survey method. Demographic information form consisting of 5 questions, "Life Satisfaction Scale" which was developed by Diener et.al. and translated into Turkish by Köker, of which reliability and validity study had been conducted and the "Alienation Scale" developed by Dean and adopted into Turkish by Kınık were applied. The obtained data were recorded in the SPSS 23 package program. Mann Whitney U test was used for comparison of binary groups and Kruskal Wallis test was used for multiple comparisons. Spearman Correlation test was applied to determine the relationship between life satisfaction and alienation level sub-dimensions. Results: It has been determined that there is a difference between life satisfaction and alienation level sub-dimension scores of disabled athletes according to the gender and marital status, that there is a difference according to life satisfaction level score and ages of 18-23, 24-29 and 18-23 and 30 and above in terms of alienation level and irregularity sub dimensions; and ages of 18-23, 24-29 and 18-23 and 30 and above in terms of social isolation sub dimension and that there is a statistically significant difference between their life satisfaction level score according to education status and alienation level sub dimension. It has been determined that there is a negative and medium sized relation between the level of alienation and life satisfaction, weakness (r = -.491, p =.050) and the irregularity (r = -.619, p =.050) sub-dimension, and that there is a positive relation between life satisfaction and social isolation sub dimension (r=.795, p= .050). Conclusions: A medium level negative relation was determined between the level of life satisfaction and alienation with gender, age, marital status and educational status and between the level of alienation with life satisfaction and weakness and irregularity sub dimensions; and a high positive relation was determined with the social isolation sub dimension.